2012
DOI: 10.3109/00365548.2012.689847
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of human T-lymphotropic virus type 1 and 2 infection in Sweden

Abstract: Since the start of screening in 1994, there has been no increased seroprevalence of HTLV-1/2 among blood donors in Sweden. Seroprevalence among Swedish IVF patients is 10 times higher than among blood donors. This finding is comparable to a 2003 European seroprevalence study of pregnant women in 7 countries. However, the possibility that the IVF group includes individuals with a higher risk of acquiring sexually transmitted infections, including HTLV, than the general population cannot be ruled out.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…The prevalence of HTLV-1 is slightly higher in countries with high immigration from HTLV-1 endemic regions (mainly Portugal, Spain, France, UK) (22). In addition, higher frequencies of HTLV-2 have been described among PWID (around 3%) in Sweden (23), (around 10%) in Spain and Italy (12–14), and among HIV+ PWID (14.6%) in Ireland (15). In Eastern Europe, the data regarding the prevalences of HTLV-1 and HTLV-2 is largely absent except a single study from Romania where the prevalence of HTLV-1 was shown to be 0.053% among blood donors (20).…”
Section: Resultsmentioning
confidence: 99%
“…The prevalence of HTLV-1 is slightly higher in countries with high immigration from HTLV-1 endemic regions (mainly Portugal, Spain, France, UK) (22). In addition, higher frequencies of HTLV-2 have been described among PWID (around 3%) in Sweden (23), (around 10%) in Spain and Italy (12–14), and among HIV+ PWID (14.6%) in Ireland (15). In Eastern Europe, the data regarding the prevalences of HTLV-1 and HTLV-2 is largely absent except a single study from Romania where the prevalence of HTLV-1 was shown to be 0.053% among blood donors (20).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, despite the PWID study participants being recruited from locations throughout Italy, all infections were classified as HTLV-2. In a more recent report using samples from group of Swedish PWIDs, the ARCHITECT ® rHTLV-I/II system was used for screening and the INNOLIA™ HTLVI/II score assay for confirmation [ 45 ], and an HTLV seroprevalence of 35/1079 (3.2%) was found. Again, the majority of HTLV infections were attributed to HTLV-2, with only two scoring positive for HTLV-1 and another five as indeterminate.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been found in locations including Central and South America, 7) Sweden, 15) Spain, 16) and Brazil, 17) and its roots are believed to lie in the indigenous peoples of areas such as the Florida peninsula of the United States, the Yucatan peninsula of Mexico, and Panama. 5) In this study, it was interesting that we detected an HTLV-2-positive infectant in China.…”
Section: )mentioning
confidence: 99%